2020
DOI: 10.3390/ma13183928
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of SLA-Based Al2O3 Microstructure During Additive Manufacturing Process

Abstract: Evolution of additively manufactured (AM) ceramics’ microstructure between manufacturing stages is a hardly explored topic. These data are of high demand for advanced numerical modeling. In this work, 3D microstructural models of Al2O3 greenbody, brownbody and sintered material are presented and analyzed, for ceramic samples manufactured with SLA-based AM workflow, using a commercially available ceramic paste and 3D printer. The novel data, acquired at the micro- and mesoscale, using Computed Tomography (CT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A crucial factor in Metal Additive Manufacturing (MAM) methods that allow the quality verification of produced parts is porosity [26][27][28][29][30][31], which is why this parameter was used for the first step selection of the produced parts for further analysis. The percentage of porosity in all produced samples ranged from 0.38% to 1.71%.…”
Section: Porosity Measurementmentioning
confidence: 99%
“…A crucial factor in Metal Additive Manufacturing (MAM) methods that allow the quality verification of produced parts is porosity [26][27][28][29][30][31], which is why this parameter was used for the first step selection of the produced parts for further analysis. The percentage of porosity in all produced samples ranged from 0.38% to 1.71%.…”
Section: Porosity Measurementmentioning
confidence: 99%
“…Recently, it has been found that alumina ceramics can be used in FDM technology, while printing the smallest overhangs or cavities is not possible with milling technology [ 143 , 147 , 149 ]. One study reported that the physical and mechanical properties of alumina ceramic samples manufactured using SLA technology are comparable to those fabricated using conventional methods [ 150 ]. Another study used SLA technology to create precise alumina crown frameworks and have found that it can reduce the marginal gap between the crown framework and the preparation of the crown by refining the SLA manufacturing process.…”
Section: Three-dimensional Printing Materialsmentioning
confidence: 99%
“…We developed a coating methodology using high-performance ceramic biologically activated with a silicate coating on alumina (AL 2 O 3 ) and coated with peptide Arg-Gly-Asp (RGD) [ 16 , 17 , 18 , 19 ]. This study investigated the osseointegration provided by ceramic functionalised with the RGD peptide in vivo.…”
Section: Introductionmentioning
confidence: 99%